Pola Komunikasi Orangtua dalam Menarik Minat Belajar Anak SD Negeri pada Masa Pandemi di Desa Kota Tengah Kabupaten Serdang Bedagai - M. Fajar Pahrozi; Maraimbang Daulay; Muhammad Alfikri (Hijaz: Jurnal Ilmu-Ilmu Keislaman, 2022)
This article aims to discuss parental communication patterns in attracting public elementary school children's learning interest during the pandemic in Kota Tengah Village, Serdang Bedagai Regency. Since the Covid-19 pandemic, the world of education has experienced quite significant changes. Learning that was originally carried out in person or offline changed to online or online. Of course this has an impact on children's interest in learning. In this case the role of parents at home is certainly very necessary in order to attract children's interest in learning. This article uses descriptive qualitative research. The data source in this study used the snowball sampling technique. The research results were obtained through observation, interviews and documentation. The results of the study show that there are several communication patterns used by parents in attracting their children's interest in learning during this pandemic, namely permissive communication patterns, authoritarian communication patterns, democratic communication patterns (authoritative).